An ultra – wideband compact meander line antenna for brain implants and biotelemetry applications in the 2.45 GHz ISM band - Archana Mohan; Niraj Kumar (Results in Engineering)
This paper proposed the meander line based wideband implantable antenna for brain implant applications operated at the industrial, scientific and medical (ISM) band (2.4 – 2.48 GHz). The proposed antenna, with minuscule dimensions of 10mm×10mm and 0.635 mm thickness of Rogers RT/Duroid 6010 material (εr=10.2,tanδ=0.0023) is adopted as a substrate and 0.2 mm thickness of superstrate layer. Incorporating a meandering line as a radiator and shorting pin allows impedance matching, minimizes antenna area, and enhances bandwidth. To evaluate the efficacy of the implantable antenna, a homogeneous brain phantom and a seven-layer heterogeneous brain phantom, both are used. The heterogeneous brain phantom includes, layers of skin, fat, cortical bone, dura, cerebrospinal fluid, grey and white matter. The proposed antenna was located below the dura and in the cerebrospinal fluid at the depth of 15.5 mm. The proposed antenna was fabricated and validated the result using mimicking gel as well as in minced pork, the obtained peak gain is -17.3 dBi and the impedance bandwidth is 828 MHz. The specific absorption rate was calculated both the seven-layer brain phantom model [516 W/kg (1-g) and 82 W/kg (10-g)] and realistic human head model [232.7 W/kg (1-g) and 48.65 W/kg (10-g)] meets the IEEE safety requirements, ensuring brain tissue safety. Furthermore, to confirm the stability and dependability of the biotelemetry link and verify the coverage of implantable antenna the link budget analysis is carried out for 10-meter distance.